SISTEM PENDUKUNG KEPUTUSAN SELEKSI MAHASISWA BARU KELAS KERJASAMA DI POLITEKNIK NEGERI MALANG - Adevian Fairuz Pratama; Rudy Ariyanto; Yan Watequlis Syaifudin (SENTIA 2016, 2016)
The great numbers of cooperation class participant enthusiasts at State Polytechnic of Malang has given a particular challenge for Polinema to provide an appropriate, effective and efficient decision in its data management for the qualified participants. TOPSIS is a method in which its best chosen alternatives have not only the shortest distance from the positive ideal solution but also the longest distance from the negative ideal solution. The criteria used in this system are based on the survey given to the committee of Admissions namely scholastic aptitude test score, psychotest score, and six other interview criteria i.e. integrity, customer service orientation, achievement orientation, continuous learning, adaptability and impact. The research results revealed that the data of participant who were succeeded and had come to the interview phase were put into the system which in turn calculated the selection results using TOPSIS method, by searching for the furthest distance and the nearest of the positive and negative ideal solution. Participants with the highest preference value (v) ranked the top in this system in accordance with the specified quota.